What democratic policing is … and is not - Bonner, Michelle D. (Policing and society, 2020)
Democratic policing is a multidimensional, multilevel, and contested concept rooted in political ideology. It is not singular or politically neutral. I argue there are four typologies of democratic policing: right, centre-right, centre-left, and left. In Latin America, in the 1980s and 1990s, countries went through the dual processes of democratisation and the implementation of neoliberal economic policies. The latter increased inequality in wealth and led to deeply divisive debates regarding the place of equality and violence in the definition of democracy. Putting aside these debates on the meaning of democracy, police reform projects in Latin America have embraced community-oriented policing as synonymous with democratic policing. Yet, democratic policing is not a singular concept and political debates matter to its various meanings. The article uses Goertz’s (2006. Social science concepts: a user’s guide. Princeton University Press) three-level concept analysis to assess the theoretical similarities and differences between the four types of democratic policing. It then tests the theory with empirical data from the cases studies of Argentina (Menem and Kirchners) and Chile (Bachelet and Piñera). The case studies are informed by field research in both countries (2006-2015), and draw on media and human rights reports as well as secondary data. The study finds a gap between theory and practice that calls for more research on policy convergence. More importantly, it reveals the need to situate ideal definitions of democratic policing within political debates on democracy, paying close attention to the role of political ideology.